Accounting logistic service through data quantification - Rusanovska, O. (Видавництво Львівської політехніки, 2016)
The importance of logistics enterprises was established for their overall economic result (profit). Emphasized that effective management of logistics activities of enterprises allows enterprises to improve the image and increase its competitiveness not only in the current time period, but also in the future. The importance of logistics services to companies was revealed and research papers based on domestic and foreign scientists, found a lack of theoretical and practical framework for the logistics service of company stressed the need for quantifying the logistic service and found free of developments on the chosen topic. Research scientists share Importance possible to identify indicators of services, among which an important place occupied by figures of logistics services, namely receiving orders 4.2 % return of 2.6 % replacement of goods 1.6 %, 1.1 repair products, technical consultancy 2 % et al., particles ranging importance of service companies show that ranks first performance of logistic service companies. The key objectives of the article include: identification of possible goals and objectives of logistics services and establish ways of quantifying the logistic service company. Why was this study the possible objectives and tasks of logistic service companies on the example of PC “Almazinstrument” and suggested ways of keeping logistic service through an existing quantification data service and built plans. Highlighted two methods of accounting logistics services: first – account already existing services, which includes compliance with these rules – formation table of the existing plan logistics services, the box in front of the customer and the specific item of logistic service put the number “1” after he was executed; If the client does not need the realization on the part of the enterprise service a particular item, it also put the number “1” (to simplify maintenance of general accounting software logistics services); where there was a need to perform certain maintenance item, but it was not implemented for various reasons, put the number “0”; under “amount” for the period necessary to put down the result of calculating the following formula: the ratio of the value in each cell to the amount of served customers. Second – accounting plans logistics service that requires compliance with the following rules: set time limits specific tasks aimed at achieving the objectives are recorded in the plan; installation planned values controlled rate; strict observance of periods of monitoring and recording actual values, using the scale of logic (Boolean) data type; in case of deviation, which does not fit the defined limits, conduct a detailed study of the problem, followed by the formation of advisory opinion to guide. The results of the study allow to formalizing and concretizing plans logistics service there by improving logistics management services and processes associated with controlling and adjusting plans for logistics services. Taking into account the results of the research as well as modern advances in information technology, possible to emphasize the need to develop automated accounting software company logistics service. Визначено важливість логістичної діяльності підприємств для їхнього загального економічного результату (прибутку). На основі дослідження праць вітчизняних та зарубіжних науковців встановлено недостатню теоретичну та практичну базу щодо логістичного обслуговування підприємства, виявлено необхідність кількісного обліку логістичного обслуговування та відсутність напрацювань щодо обраної тематики. Досліджено можливі цілі та завдання логістичного обслуговування підприємств на прикладі ПАТ “Алмазінструмент” та запропоновано способи обліку логістичного обслуговування через квантифікацію даних уже наявного обслуговування та побудованих планів.
Облік логістичного обслуговування через квантифікацію даних
Keywords: logistics services; data quantification; efficiency and effectiveness of operations; логістичне обслуговування; квантифікація даних; ефективність та результативність діяльності